The Influence Of Macroeconomics And Financial Risks On Islamic Corporate Social Responsibility Diclosure Through Earnings At Sharia Commercial Banks In Indonesia - Lu’lu’il Maknuun (Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Purpose - This study aims to analyze the effect of Macroeconomics and Financial Risk on Islamic Corporate Social Responsibility Disclosure (ICSRD) through Earning in Islamic Commercial Banks in Indonesia.Method - This study uses a quantitative method using secondary data in the form of financial risk data, earnings and ICSRD from annual financial reports at Islamic Commercial Banks and published macroeconomic data at the Central Bureau of Statistics from 2017 -2021. The analytical method used is SEM analysis using the SmartPLS 2.0 analysis tool.Result - The results showed that macroeconomics had a significant effect on ICSRD but did not have a significant effect on earnings. Financial risk has a significant effect on ICSRD but does not have a significant effect on earnings. Earning has no significant effect on ICSRD. Earning is not able to mediate Macroeconomics on ICSRD but is able to mediate financial risks on Islamic Corporate Social Responsibility Disclosure (ICSRD) at Islamic Commercial Banks.Implication - This research utilizes data from Islamic commercial banks in Indonesia and the Central Statistics Agency for the years 2017-2021.Originality - This research discusses the profits obtained by companies used for the disclosure of social responsibility of Islamic commercial banks in Indonesia to society, taking into account internal and external factors of the company, namely macroeconomics and financial risk.